2018
DOI: 10.1002/slct.201800421
|View full text |Cite
|
Sign up to set email alerts
|

A De Novo Approach for the Stereoselective Synthesis of Cyclopenta[c]pyranone Scaffold Present in Iridoids: Formal Syntheses of Isoboonein, Iridomyrmecin and Isoiridomyrmecin

Abstract: A conceptually new intramolecular Pauson-Khand reaction (IPKR) based general strategy has been demonstrated for the formal syntheses of isoboonein, iridomyrmecin and isoiridomyr-mecin from very cheap, commercially available starting material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Thus, several fantastic synthetic pathways for their total synthesis have been reported. 88 Some of them are accomplished and reported by Suh and co-workers 89,90 and recently one reported by Chakraborty and co-workers. 91 In spite of the appearance of these reports among the others, a literature survey disclosed few reports on the total synthesis of diverse oxy-functionality pattern observed on the cyclopentane ring of the iridoid framework.…”
Section: Applications Of Pauson–khand Reaction In the Total Synthesis...mentioning
confidence: 93%
See 2 more Smart Citations
“…Thus, several fantastic synthetic pathways for their total synthesis have been reported. 88 Some of them are accomplished and reported by Suh and co-workers 89,90 and recently one reported by Chakraborty and co-workers. 91 In spite of the appearance of these reports among the others, a literature survey disclosed few reports on the total synthesis of diverse oxy-functionality pattern observed on the cyclopentane ring of the iridoid framework.…”
Section: Applications Of Pauson–khand Reaction In the Total Synthesis...mentioning
confidence: 93%
“…For example, the total synthesis of 7-epiboschnialactone 68 0 . This strategy is started with the easily accessible glycerol acetonide 56, 88,95 which in two steps was converted into the enyne 57 as an appropriate precursor of PKR. The latter in crucial step was subjected to diastereoselective conventional IPKR 88 in the presence of Co 2 (CO) 8 , TMNO to afford compound Scheme 9 Total synthesis of (+)-mintlactone 54 and (À)-isomintlactone 55.…”
Section: Monoterpenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nickel borideconveniently prepared from nickel salts and NaBH 4 has been utilized for a variety of reductive transformations such as olefin hydrogenation, dehalogenation, and desulfurization . Inspired by recent work of Khan et al, who demonstrated the diastereoselective reduction of cyclopentenone in a fused bicyclic system, we tested deuteration of (±)- 6 using nickel boride generated in situ from NiCl 2 · 6H 2 O and NaBD 4 in MeOD (Table , entry 4). The reaction exclusively formed, albeit sluggishly, the cis -fused product 7 in 45% yield.…”
mentioning
confidence: 99%